Ultrasensitive Doppler as a tool for the diagnosis of testicular ischemia during the Valsalva maneuver: a new way to explore varicoceles?. (August 2019) - Rocher, Laurence; Gennisson, Jean-Luc; Baranger, Jérôme; Rachas, Antoine; Criton, Aline; Izard, Vincent; Bertolloto, Michele; Bellin, Marie-France; Correas, Jean-Michel
Background: Varicocele is among the most common causes of male infertility because of various mechanism, including hypoxia. Purpose: To evaluate testicular vascularization (TV) with ultrasensitive Doppler before and during the Valsalva maneuver (VM) and correlate TV changes to varicocele's spermatic venous reflux graduated by color Doppler. Material and Methods: From January to February 2016, 69 men (135 testis) referred for scrotal ultrasound were prospectively enrolled. An institutional review board approved the study. As gold standard, the spermatic venous reflux in the supratesticular region was assessed with color Doppler ultrasound and graded from 0 to III. A new ultra-sensitive Doppler (USD) sequence was performed on testicular parenchyma in an axial view. The TV changes before and during the VM were qualitatively graded from 0 to 2 using a visual scale by consensus. The vessels surface was quantified using customized MATLAB® software, and compared to the testicular delineated surface, resulting in a vessels surface ratio (VSR). The absolute and relative VSR difference before and during the VM was calculated. The qualitative scale and the quantitative VSR changes were compared with the spermatic venous reflux grade using an analysis of variance. Results: A strong correlation has been found between the spermatic venous reflux grade and TV decrease during the VM using USD, for qualitative graduation as well as for quantitative measurement ( P < 0.0001). Conclusion: TV assessed by USD decreased significantly during the VM in patients with varicocele; this decrease was significantly associated with spermatic venous reflux grade.